Project Managemet Issues in the Public Administration System of RA - Saribekyan, Amalya; Gyozalyan, Vardush (Bulletin of Yerevan University G: Economics, 2020)
Project management as a key component of program development and program management is not yet fully used in the public administration system of the Republic of Armenia. This is primarily due to the imperfections of standards and approaches for the development and management of government programs, the underestimation of the importance of interactions between projects and programs in the process of program development, the limited use of project management tools, in particular, network planning methods, and the lack of specialized project managers in the field of implementation of government programs. In highlighting these issues, the authors emphasize the formation of an institutional body whose main purpose is to foster project management to the implementation of public programs.
Keywords: public administration, state program, program management, project management, state project, network planning, program development concept, strategy